Electrochemical Activity of Glutathione at a Graphite Electrode Modified with Gold Nanoparticles; Oriental journal of chemistry; Vol. 31, № 2 - Perevezentseva D. O. Dariya Olegovna; Skirdin K. V. Kirill Vyacheslavovich; Gorchakov E. V.; Bimatov V. I. (2015, 2015)
Title screen